2000
DOI: 10.1136/gut.47.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proinflammatory interleukins on jejunal nutrient transport

Abstract: Aim-We examined the eVect of proinflammatory and anti-inflammatory interleukins on jejunal nutrient transport and expression of the sodium-glucose linked cotransporter (SGLT-1). Methods-3-O-methylglucose and L-proline transport rates were examined in New Zealand White rabbit stripped, short circuited jejunal tissue. The eVects of the proinflammatory cytokines interleukin (IL)-1 , IL-6, and IL-8, IL-1 plus the specific IL-1 antagonist, IL-1ra, and the anti-inflammatory cytokine IL-10 were investigated. In separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 53 publications
3
44
1
2
Order By: Relevance
“…22 This is at variance to D-glucose, which uses SGLT-1 for absorption from the gut. 23 This finding supports the hypothesis that also in the present setting, as we had observed previously for LPSinduced shock, a specific D-glucose-SGLT-1 interaction is required to achieve protection from hepatic injury. Similarly, no protection from LPS/ D-GalN-induced liver injury is observed on oral administration of the disaccharide sucrose.…”
Section: Discussionsupporting
confidence: 93%
“…22 This is at variance to D-glucose, which uses SGLT-1 for absorption from the gut. 23 This finding supports the hypothesis that also in the present setting, as we had observed previously for LPSinduced shock, a specific D-glucose-SGLT-1 interaction is required to achieve protection from hepatic injury. Similarly, no protection from LPS/ D-GalN-induced liver injury is observed on oral administration of the disaccharide sucrose.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Stouthard et al (40) studied patients with metastatic renal cell cancer receiving rhIL-6 infusion and observed an increase in glucose appearance and whole body glucose disposal when the isotopic tracer dilution method was used. In addition, Stouthard et al (39) demonstrated that IL-6 enhanced both basal and insulin-stimulated glucose uptake in cultured 3T3-L1 adipocytes, and Hardin et al (11) observed increased glucose transport in jejunal tissue incubated with IL-6 compared with controls. Therefore, a phasic increase in IL-6 may have an important biological role, as previously suggested (6,27).…”
Section: Discussionmentioning
confidence: 99%
“…These authors demonstrated that treating 3T3-L1 adipocytes with recombinant murine IL-6 for 5 h increased basal glucose transport by ~20%. An increase in IL-6-stimulated basal glucose transport has also been observed in both smooth muscle [67] and chondrocytes [68], although this effect is not always seen, as two studies have found no effect of IL-6 on basal glucose transport in 3T3 L1 adipocytes [55,69].…”
Section: Interaction Between Il-6 and Glucose Transport In Vitromentioning
confidence: 99%